Tonic Seizure Status Epilepticus Triggered by Valproate in a Child with Doose Syndrome - Grande-Martín, Alberto; Pardal-Fernández, José Manuel; Carrascosa-Romero, María Carmen; De Cabo, Carlos (Neuropediatrics, 2016)
Antiepileptic drugs may occasionally increase seizure frequency or eliciting de novo seizure occurrence; the underlying mechanism of these effects is not known. The potential adverse effects of valproic acid in myoclonic astatic epilepsy have been noted by experienced clinicians in various different regions of the world, but this important observation has not been sufficiently reported. We present the case of tonic status epilepticus in an 8-year-old boy with Doose syndrome related to valproic acid. Valproic acid, such as others antiepileptic drugs, is liable to produce paradoxical effects such as the atypical seizures we report. We emphasize the importance for the management of acute seizures in an intensive care unit setting and increase awareness of the acute toxic effects of antiepileptic drugs.
Keywords: antiepileptic drugs; Doose syndrome; electroencephalogram; epilepsy; paradoxical antiepileptic effects; seizure